Pengaruh Infrastruktur Transportasi dan Urbanisasi Terhadap Pertumbuhan Ekonomi di Negara ASEAN - Rizki Revinski; Melti Roza Adry; Urmatul Uska Akbar (Universitas Negeri Padang, 2022)
This research was conducted to see of transportation infrastructure and urbanization on economic growth in ASEAN countries with the chosen model being the Commont Effect Model (CEM). The data used is panel data for the period 2008-2019, which was obtained from the world bank. The variables used are Transportation Infrastructure (X1) and Urbanization (X2). The research method used is: Ordinary Least Square (OLS). The results show that transportation infrastructure has a negative and significant effect on economic growth, while urbanization has a negative and insignificant effect on economic growth in ASEAN countries. Together, transportation infrastructure and urbanization affect economic growth in ASEAN countries.